Beyond the Tracks: Railway Stations as Sites of Inclusion and Social Fluidity in Biswanath Ghosh’s Chai, Chai: Travels in Places Where You Stop But Never Get Off - Poudel, Uttam (Literary Studies, 2026)
This paper discusses Biswanath Ghosh’s Chai, Chai as a travelogue that reveals India’s often-overlooked railway towns, showing them as welcoming spaces where identities, social status, and class blend together in the flow of travel. While many stories about India focus on the metropolis, Ghosh highlights stations like Itarsi, Mughal Sarai, and Jhansi, which are usually seen as just places to pass through but are actually full of human stories about flexibility, survival, and togetherness. By applying Henri Lefebvre’s ideas about space, this study looks at how railway stations act as lively and democratic spaces where social differences fade away in the constant movement of people. Victor Turner’s concepts of “liminality” and “communitas” help understand how these spaces encourage cultural mixing and flexible identities. Judith Butler’s idea of performativity as a dynamic process shaped by repeated performances in various contexts illustrates how vendors, laborers, and travelers play different roles, transforming these stations into ever-changing stages of life. More than just places to catch a train, railway stations teach us important lessons about social inclusion and diversity. People from various backgrounds interact daily, learning to coexist despite their differences. This study argues that Ghosh’s depiction of railway towns challenges the strict structures of mainstream society, showing that diversity can thrive in motion. By observing these spaces, we can learn to embrace inclusion, adapt to our differences, and work towards a more harmonious future.